(untitled) (Bangladesh Journal of Botany, 2026)
Microclimate, wheat growth and productivity were evaluated in agriculture (AP) and agroforestry plot (AFP). Results showed the difference of air temperature (3.83°C), relative humidity (6.6%), soil temperature (2.3°C), and moisture (5%) between AP and AFP. Similarly, tiller height (114.9 cm), spike length (12.1 cm), number of tillers m-2 (413), grain weight m-2 (364.6 g) and 1000 grain weight (50.2 g) were found significantly high at 12.5 ft from tree stem in AFP as compared to AP. CO2 assimilation rate (15.4 mmol m-2 s-1), stomatal conductance (0.41 mmol mol m-2 s-1) and transpiration rate (4.3 mmol mol m-2 s-1) was also found highest in wheat at 12.5ft as compared to AP. Overall, wheat productivity remained similar in AFP as compared to AP. Therefore, it can be concluded that AFP can ameliorate in microclimate and productivity under changing climate. Bangladesh J. Bot. 55(2): 329-334, 2026 (June)